Exploring exhibition design: designing experiences for data visualization - Rajan, Arundathi (InfoDesign, 2025)
This paper explores how exhibition design can contribute to Information Design by conceptualizing experiences to promote tangible data explorations. It examines how spatial experiences and tangible user interfaces can make data visualization more accessible, reducing intimidation linked to technical tools. Through a data visualization project and a data collection experiment conducted at an academic conference, the paper highlights exhibition-based approaches to bridge this gap. It argues for a shift in focus toward the process of data-making itself, emphasizing its significance alongside the data it generates.